Pengaruh Budaya Organisasi dan Kepuasan Kerja terhadap Kinerja Karyawan Universitas Islam ”45” Bekasi - Syahyono . (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2017)
This research was conducted in Unisma Bekasi. Data were collected by using a questionnaire, and sampling this study as many as 50 employees of probability sampling. The data analysis method used is multiple regression test, F test, and the coefficient of determination (R ²)The results showed that: 1). Partially organizational culture t test variable (X1) effect on the performance of employees at Unisma Bekasi. It is known from p-value less than 0.05. 2). Partially Job Satisfaction variable t test (X2) effect job satisfaction of employees at Unisma Bekasi. It is known from p-value less than 0.05. 3). Simultaneously (F test) organizational culture and Job Satisfaction, has a significant influence on employee performance in Unisma Bekasi. It is known from p-value less than 0.05